PRESIDENT DIRECTOR TENURE AND EARNINGS MANAGEMENT - Hetty Muniroh (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2016)
CEO tenure related of earnings management. This study also examine whether the earnings management are differencebetween early CEO tenure and final CEO tenure. The population this study is publicly traded companylisted on the Indonesia Stock Exchange (IDX) in 2010-2013, best on the purposive sampling method, the total sample is 212 companies. This study use two models to examine earnings management by Jones Modified modeland Roychowdury model, namely discretionary accrual model and abnormal discretionary expenses. The method of analysis in this study is paired samples t Test. The result of this study shows paired samples t Test indicate that earnings management issignificantly different between in the early years and final years of CEO tenure.